2010
DOI: 10.1145/1833351.1778802
|View full text |Cite
|
Sign up to set email alerts
|

Real-time lens blur effects and focus control

Abstract: (b) (c) (d) (a)Figure 1: Example images rendered in real time by our method. We achieve near-accurate depth-of-field effects, including lens aberrations (e.g., spherical aberration, (a)). The efficiency of our method makes it well-suited for artistic purposes and we support complex simulations like tilt-shift photography (b). Further, our system offers an intuitive control of depth of field and we extend the physical model (c) to achieve an expressive, yet convincing result (d) (here, the background statues st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…HsienChe Lee [10] models a generic optical system, however, our measurements show that there are strong dependencies on the particular lens being used. Sungkil Lee et al [11] describe optical aberrations from a rendering perspective and note that these effects are often present in real imagery. Gu et al [5] develop methods to correct dirty or partially occluded optics and Raskar et al [15] model glare in lenses.…”
Section: Related Workmentioning
confidence: 99%
“…HsienChe Lee [10] models a generic optical system, however, our measurements show that there are strong dependencies on the particular lens being used. Sungkil Lee et al [11] describe optical aberrations from a rendering perspective and note that these effects are often present in real imagery. Gu et al [5] develop methods to correct dirty or partially occluded optics and Raskar et al [15] model glare in lenses.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, we explicitly deal with visibility based on the similarity of the apparent trajectories of the samples in the temporal light field. Lee et al [2010] blur the distinction between sampling and reconstruction. They accelerate defocus effects by first rasterizing the scene into a layered depth image (LDI), and then performing fast ray tracing using the LDI as a scene representation.…”
Section: Reprojection Techniquesmentioning
confidence: 99%
“…Comparing with single-image blurring methods, 25,26 our light field-based analysis is good at reducing two types of boundary artifacts: the boundary discontinuity and intensity leakage artifacts. We summarize four types of boundary artifacts and analyze them separately.…”
Section: Comparison Of Our Methods and Single-imagementioning
confidence: 97%
“…Previous studies suggested that the real-time DoF effects can be obtained by applying a spatially varying blur on the color image and using the disparity value to determine the size of the blur kernel. 25,26 However, this method suffers from strong intensity leakage and boundary bleeding artifacts. Other methods such as distributed ray tracing 27 and accumulation buffer 28 give more accurate results.…”
Section: Dof Renderingmentioning
confidence: 99%